2022
DOI: 10.24275/rmiq/bio2701
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical model to estimate volumetric oxygen transfer coefficient in bioreactors using conformable calculus

Abstract: totales del petróleo intemperizados en suelos y sedimentos (Biodegradation modeling of sludge bioreactors of total petroleum hydrocarbons weathering in soil and sediments)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…However, the result of the application of simulation tools is heavily dependent on the quality of the mathematical model (Carrillo-Ahumada et al, 2020;Nogales et al, 2022;Buddhakulsomsiri et al, 2018;Maraphum et al, 2022;Melgarejo-Torres et al, 2022;Gutierrez-Antonio et al, 2022). Also, it has been observed that the process dynamics are nonlinear, which has made the modeling task even more complex (Feil et al, 2004;Castillo-Santos et al, 2017;Toro et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, the result of the application of simulation tools is heavily dependent on the quality of the mathematical model (Carrillo-Ahumada et al, 2020;Nogales et al, 2022;Buddhakulsomsiri et al, 2018;Maraphum et al, 2022;Melgarejo-Torres et al, 2022;Gutierrez-Antonio et al, 2022). Also, it has been observed that the process dynamics are nonlinear, which has made the modeling task even more complex (Feil et al, 2004;Castillo-Santos et al, 2017;Toro et al, 2018).…”
Section: Introductionmentioning
confidence: 99%